A Flexible Na3V2(PO4)3/C Composite Fiber Membrane Cathode for Na-Ion and Na-Li Hybrid-Ion Batteries. Issue 9 (9th June 2018) - Jing, Mao-xiang; Zhang, Ji; Han, Chong; Yang, Hua; Yao, Shan-shan; Zhu, Lin; Chen, Li-li; Xie, Qing-long; Chen, Xiang; Shen, Xiang-qian; Qin, Shi-biao
Abstract : High electronic conductivity and ionic conductivity are important for Na3 V2 (PO4 )3 (NVP) to be used in Na-ion and Na-Li hybrid-ion battery. In this work, a three dimentional (3D) Na3 V2 (PO4 )3 /C (NVP/C) fiber membrane with nano carbon-coated NVP particles uniformly embedded on the surface of carbon fibers was successfully prepared by a modified electrospinning technique. The combined use of polyacrylonitrile (PAN) and polyvinylpyrrolidone (PVP) in the fiber precursor promotes the distribution of NVP particles and maintains the stability of 3D long-range conductive networks. The NVP/C fiber membrane can be used as self-standing cathodes for Na-ion battery. The discharge capacity of the NVP/C-Na battery is 110.9, 108.1, 104.6, 104.3, 95.6 and 72.4 mAh/g at the current densities of 0.1C, 0.2C, 0.5C, 1C, 5C and 10C, respectively. After the rate tests, the Na3 V2 (PO4 )3 /C fiber membrane cathode still exhibits excellent cycle stability at 0.5C, 5C and 10C with a retention discharge capacity of 102, 87.9 and 57.1mAh/g after 100 cycles. Simultaneously, this NVP/C fiber membrane can also be used as cathodes for Na-Li hybrid-ion battery, and shows good electrochemical performance in the voltage range of 2.5–4.8 V. This 3D fiber membrane electrode shows a great potential in the use of flexible Na-ion and Na-Li hybrid ion batteries.